Impact of Yttrium Dopant on Physical Properties of Manganese Selenide Nanoparticles synthesized via Spray Pyrolysis for Photovoltaic Applications - Greatman M Onwunyiriuwa; Lebe A Nnanna; Nwamaka I Akpu; Young C Ahameful; Maxwell O Akpu (Physics Access, 2025)
Undoped and yttrium-doped manganese selenide thin films were synthesized via spray pyrolysis deposition technique for photovoltaic purposes by utilizing manganese (II) acetate tetrahydrate, selenium (iv) oxide and yttrium. The deposited samples were characterized with instruments such as X-ray diffractometry, Uv-Vis spectrophotometry, four-point probe and SEM/EDX for structural, optical, electrical and morphological analysis. The X-ray diffraction pattern for both undoped and Y-doped MgSe samples shows the presence of crystal peaks along (111), (200), (210), (211) and (300) planes indicating polycrystalline and hexagonal structural nature. Optical analysis reveals a decrease in absorbance and an increase in transmittance as the wavelength increases for all the samples. The addition of a higher percentage (0.04 mol%) of yttrium dopant narrowed the bandgap energy (1.15 eV) of the undoped MnSe, making these materials promising for solar cell fabrication. Electrical analysis reveals that as yttrium dopant concentration in MnSe increases from 0 to 0.04 mol%, the film thickness increases from 110.0 nm to 115.13 nm with increasing resistivity and decreasing conductivity of 11.68 x 10-4 to 11.68 x 10-4 Ω.m and 8.561 x 102 to 8.467 x 102 (Ω.m)-1 respectively. The overall electrical result of both undoped and y-doped MnSe conforms to that of a typical semiconductor. For the morphology result, the addition of yttrium dopant altered the microstructure of undoped MnSe. For undoped MnSe a smooth dense layer was observed while Y-doped MnSe reveals an agglomeration with no defined shape but is also dense. EDX result confirms the growth of a novel yttrium manganese selenide (YMnSe) thin material. YMnSe films offer features like narrowed band gap energy, improved charge transport characteristics and enhanced light trapping, making them potential materials for photovoltaic applications.